Enhanced sinterability and electrical properties of Bi2O3-added Ba0.85Ca0.15Zr0.1Ti0.9O3ceramics - Piyaporn Jaimeewong (2018)
© 2017 Taylor & Francis Group, LLC. The ceramics of Bi 2 O 3 -added Ba 0.85 Ca 0.15 Zr 0.1 Ti 0.9 O 3 or BCZT-xBi (where x = 0.005, 0.01, 0.02 and 0.1 mol fraction) were fabricated from sol-gel auto-combustion derived BCZT and commercial Bi 2 O 3 powders. In this study, BCZT-0.02Bi ceramic sintered at 1200°C for 2 h was found to be the optimum composition with high relative density and homogeneous microstructure. The temperature at maximum dielectric constant (T max ) of this sample was near room temperature, rendering a high dielectric constant value (∼1653). Frequency dependence of T max suggested the relaxor behavior which was also supported by slim ferroelectric hysteresis loops. Since a relatively large breakdown voltage ( > 70 kV/cm) was observed, the BCZT-0.02Bi ceramic could be a potential lead-free electrostrictive/piezoelectric material for actuator applications.